THE ROLE OF PSYCHODIAGNOSTICS IN UNDERSTANDING THE MENTAL HEALTH OF MODERN INDIVIDUALS - Setiawan, Agus; Iskandar Dinata, Konto (International Journal of Multidisciplinary Reseach, 2025)
Psychodiagnostics is a crucial field in modern psychology, serving to objectively and comprehensively assess, measure, and understand an individual's mental health. Amidst the dynamics of 21st-century life, characterized by high demands, social pressures, and an increase in mental disorders, the need for systematic psychological assessment is growing. This article aims to examine the role of psychodiagnostics in understanding the mental health of modern individuals through an analysis of various assessment methods, such as psychological testing, clinical interviews, observation, inventory scales, and documentation analysis. A multidimensional approach to psychodiagnostics enables early identification of psychological disorders, mapping risk factors, and providing appropriate intervention recommendations. The findings indicate that psychodiagnostics serves not only as a detection tool but also as a basis for decision-making in clinical interventions, therapy planning, and monitoring mental health development. Thus, psychodiagnostics plays a strategic role in improving the psychological well-being of modern individuals through valid, reliable, and evidence-based assessments.